2019
DOI: 10.1111/os.12600
|View full text |Cite
|
Sign up to set email alerts
|

Limited Influence of Comorbidities on Length of Stay after Total Hip Arthroplasty: Experience of Enhanced Recovery after Surgery

Abstract: Objectives To identify predictors of length of stay (LOS) after total hip arthroplasty (THA) in an enhanced recovery after surgery (ERAS) program and evaluate the safety and cost‐efficiency of the ERAS program with reduced LOS for unselected patients in a Chinese population. Methods A total of 311 consecutive, unselected patients undergoing primary THA at a single institution were retrospectively reviewed and divided into two groups: LOS ≤ 3 and LOS > 3 group. All patients were managed with the same ERAS proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 40 publications
(111 reference statements)
4
44
0
Order By: Relevance
“…These pathologies, as shown by some studies, can interfere with the rehabilitation of the patient, increasing the length of hospital stay 49,50 . However, this is not unanimous in the literature, as other studies have not found this relationship 51 . Therefore, we believe that despite being a limitation of our study, it may not have a great impact since all patients undergo a clinical evaluation prior to surgery, as well as a careful pre-anesthetic evaluation, which means that the patients are clinically stable and have their pathologies adjusted.…”
Section: Study Limitationsmentioning
confidence: 70%
“…These pathologies, as shown by some studies, can interfere with the rehabilitation of the patient, increasing the length of hospital stay 49,50 . However, this is not unanimous in the literature, as other studies have not found this relationship 51 . Therefore, we believe that despite being a limitation of our study, it may not have a great impact since all patients undergo a clinical evaluation prior to surgery, as well as a careful pre-anesthetic evaluation, which means that the patients are clinically stable and have their pathologies adjusted.…”
Section: Study Limitationsmentioning
confidence: 70%
“…15 Thromboprophylaxis was started in a timely manner: a half dose of low-molecular weight heparin (0.2 mL 2000 IU) was given to patients 6 h postoperatively, and a full dose (0.4 mL 4000 IU) was given at 24 h intervals in the subsequent days by subcutaneous injection till the day of discharge. 16 The criterion of blood transfusion was set as haemoglobin (Hb) level of <70 or 70~100 g/L but with symptomatic anaemia (defined as severe mental status changes, palpitations and/or pallor).…”
Section: Perioperative Managementmentioning
confidence: 99%
“…All patients were encouraged to conduct isometric exercises and active motions while in bed immediately after surgery. All patients were treated with antibiotic prophylaxis and deep venous thromboembolism prophylaxis postoperatively [14]. Generally, the patients were mobilized with partial weight-bearing at 1 to 4 weeks after surgery depending on the degree of bone defect.…”
Section: Surgical Techniquementioning
confidence: 99%